2022
DOI: 10.32859/era.24.4.1-24
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based veterinary practices in Jammu and Kashmir: A review of the trends, transfer and conservation of traditional ethnoveterinary knowledge

Abstract: Background: Traditional veterinary phytotherapy refers to the use of plants for promoting health and curing diseases of livestock. Animal rearing is the major occupation of the tribal communities in Jammu and Kashmir and is thus an important part of their economy. Due to the inaccessibility of modern facilities and allopathic drugs, these communities mainly rely on the local flora to cure common ailments prevalent in livestock, developing a rich knowledge of ethnoveterinary practices. These practices are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…For ethnoveterinary uses, the local people of Paddar prepared different herbal formulations, including powder, raw, paste, and oil (Table 2). Similar use of such formulations for ethnoveterinary purposes has been reported from J&K (Khateeb et al 2015;Dutta et al 2022;Hassan et al 2022), and other Himalayan regions (Ali et al 2019;Prakash et al 2021).…”
Section: Plant Part Used Mode Of Preparation and Administrationsupporting
confidence: 68%
“…For ethnoveterinary uses, the local people of Paddar prepared different herbal formulations, including powder, raw, paste, and oil (Table 2). Similar use of such formulations for ethnoveterinary purposes has been reported from J&K (Khateeb et al 2015;Dutta et al 2022;Hassan et al 2022), and other Himalayan regions (Ali et al 2019;Prakash et al 2021).…”
Section: Plant Part Used Mode Of Preparation and Administrationsupporting
confidence: 68%
“…was used to treat alopecia and hair tonic in the present study. In contrast, the people in the Kathua and Rajouri districts of Jammu & Kashmir used raw and powder forms of seed and root to treat pneumonia, food poisoning, blood in stool & urine, and as an appetizer (Sharma & Manhas 2015;Sharma et al 2012;Dutta et al 2022). The whole plant of Ephedra gerardiana to treat cough in the present study is similar to the study conducted on Trans-Himalayan migratory shepherds in the Kannur district of Himachal Pradesh-India (Radha et al 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the area is generally referred as a " cold desert" (Gairola et al 2014) and is characterized by extreme weather conditions, marked water scarcity, short vegetation periods, and scattered vegetation, which are confined to small pockets (Ballabh et al 2008) Asteraceae and Fabaceae were the dominant families in the present study. The dominant use of plant species of these two families for ethnoveterinary purposes has also been previously reported from Jammu and Kashmir (Singh et al 2022;Dutta et al 2022). Other studies conducted in Western Himalayan regions have also reported wider utilization of Asteraceae plants in ethnoveterinary ailments (Ahmad et al 2017;Ahmed & Murtaza 2015;Wani et al 2022).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation